Perlindungan Hukum Terhadap Pembeli Rumah Bersubsidi Perspektif Kompilasi Hukum Ekonomi Syariah Di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Zainuddin Hasibuan; Tetty Marlina Tarigan (UNES Law Review, 2023)
This research departs from the case that occurred at Griya Widuri Housing, where the state and the housing organizer, namely the developer, were deemed unable to carry outtheir obligations as they should, thus sacrificing the rights that consumers should have, namely a comfortable and safe place to live. This is due to the role of unscrupulous local residents who force and threaten their comfort and security if they do not use their services as construction workers in the housing organization area. This type of research is field research. This research approach is a sociological legal approach, using qualitative methods. The location of this research was carried out at the Griya Widuri Housing complex located at Jl. Sugeng, Sumber Rejo Timur district Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The research uses primary data, namely interviews with consumers of Griya Widuri Housing, while the primary legal material is the Republic of Indonesia Supreme Court Regulation Number 2 of 2008 concerning the Compilation of Sharia Economic Law and Law Number 1 of 2011 concerning Housing and Settlement Areas. In this study, the researcher concluded that based on the Compilation of Sharia Economic Law, every transaction in Islam must be able to protect the interests and rights of consumers in replacing or covering losses experienced by consumers. So that housing developers guarantee that the quality of house buildings complies with applicable quality standards, also guaranteeing the creation of housing that is healthy, safe, harmonious and sustainable.